ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR SISWA DI SMP NEGERI 25 KOTA BENGKULU - Yunarman, Sepri; Putri Hamdana, Asrah; Sabela Putri, Ahda; Nefriyani, Anggun; Yuseftri, Gita (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
This research aims to analyze the factors that influence student learning motivation at SMP Negeri 25 Bengkulu City. The factors analyzed include internal factors, such as interest and self-confidence, as well as external factors, such as family environment, teacher support, and learning facilities. This research used a quantitative method by distributing questionnaires to 150 students as a sample. The research results show that family environmental factors and teacher support have a significant influence on student learning motivation. Apart from that, internal factors such as interest in learning also play an important role in increasing student motivation. This study provides recommendations for educators and parents to better support students in their learning process.